2009
DOI: 10.1177/0885728809336654
|View full text |Cite
|
Sign up to set email alerts
|

Self-Determination for Students with Disabilities

Abstract: Seven narrative and systematic reviews published since 2000 and focusing on self-determination for individuals with disabilities are reviewed in this narrative metasynthesis. The authors distinguish their work from other metasynthesis work by calling it a narrative metasynthesis because they include both narrative reviews and meta-analyses in this metasynthesis. These seven reviews focused on different disability groups, different intervention curricular and instructional techniques, and different outcomes. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
93
2
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(105 citation statements)
references
References 23 publications
2
93
2
6
Order By: Relevance
“…Researchers have found that multi-component interventions (i.e., interventions that teach multiple selfdetermination skills) tend to be the most effective in promoting self-determination (Cobb et al 2009), and this also is more efficient in terms of instructional time, an important consideration given the multiple demands on teacher's time. The Self-Determined Learning Model of Instruction (SDLMI; Mithaug et al 1998;Wehmeyer et al 2000b) was developed to provide a means to enable teachers to teach students to self-direct learning and learn and practice multiple self-determination skills as they set and work towards learning goals.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that multi-component interventions (i.e., interventions that teach multiple selfdetermination skills) tend to be the most effective in promoting self-determination (Cobb et al 2009), and this also is more efficient in terms of instructional time, an important consideration given the multiple demands on teacher's time. The Self-Determined Learning Model of Instruction (SDLMI; Mithaug et al 1998;Wehmeyer et al 2000b) was developed to provide a means to enable teachers to teach students to self-direct learning and learn and practice multiple self-determination skills as they set and work towards learning goals.…”
Section: Introductionmentioning
confidence: 99%
“…Without this disaggregated information, it is difficult to determine whether these evidence-based practices are effective in improving postschool outcomes for students who are Black and have disabilities or whether different approaches are needed to address differing challenges for this population. In particular, there is widespread agreement that self-determination represents a critical set of skills necessary to youth transitioning to adulthood (Storey & Miner, 2011;Wehman, 2011) and is a key component of high-quality transition services (Cobb, 2009). High student self-determination has been linked to in-school academic gains (Stodden & Dowrick, 2001) and improved post-school employment (Wehmeyer & Schwartz, 1998), post-secondary education (Raskind et al, 1999;Thoma & Getzel, 2005), and positive community living outcomes (Wehmeyer & Schalock, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Other examples of qualitative metasynthesis have emerged in the educational arena such as a metasynthesis on the impact of high-stakes testing on curricula (Au, 2007) and a partial metasynthesis combined with narrative reviews on self-determination for students with disabilities (Cobb, Lehmann, Newman-Gonchar, & Alwell, 2009). Clearly, the application of qualitative research metasynthesis has not been fully examined or realized in the field of education, but these examples illustrate the potential of this approach.…”
Section: The Promise Of Metasynthesis In Early Childhoodmentioning
confidence: 99%